In vitro evaluation of the cytotoxic and genotoxic effects of artemether, an antimalarial drug, in a gastric cancer cell line (PG100). Issue 2 (23rd September 2011) - Alcântara, Diego Di Felipe Ávila; Ribeiro, Helem Ferreira; Cardoso, Plínio Cerqueira dos Santos; Araújo, Taíssa Maíra Thomaz; Burbano, Rommel Rodriguez; Guimarães, Adriana Costa; Khayat, André Salim; de, Marcelo
ABSTRACT Artemisinin is a sesquiterpene lactone endoperoxide, obtained from Artemisia annua, and extensively used as an antimalarial drug. Many studies have reported the genotoxic and cytotoxic effects of artemisinins; however, there are no studies that compare such effects between cancer cell lines and normal human cells after treatment with artemether, an artemisinin derivative. Gastric cancer is the fourth most frequent type of cancer and the second highest cause of cancer mortality worldwide. Thus, the aim of this study was to evaluate the in vitro genotoxic and cytotoxic effects induced by artemether in gastric cancer cell line (PG100) and compare them with the results obtained in human lymphocytes exposed to the same conditions. We used MTT (3‐(4, 5‐methylthiazol‐2‐yl)‐2, 5‐diphenyl‐tetrazolium bromide) assay, comet assay and ethidium bromide/acridine orange viability staining to evaluate the cytotoxic and genotoxic effects of artemether in PG100. MTT assay showed a decrease in the survival percentages for both cell types treated with different concentrations of artemether (P < 0.05). PG100 also showed a significant dose‐dependent increase in DNA damage index at concentrations of 119.4 and 238.8 µg ml−1 (P < 0.05). Our results showed that artemether induced necrosis in PG100 at concentrations of 238.8 and 477.6 µg ml−1, for all the tested harvest times (P < 0.05). In lymphocytes, artemether induced both apoptosis and necrosis at concentrations of 238.8 and 477.6 µg ml−1, for all the tested harvest times (P < 0.05). In conclusion, human lymphocytes were more sensitive to the cytotoxic effects of the antimalarial drug than the gastric cancer cell line PG100. Copyright © 2011 John Wiley & Sons, Ltd.